All Days 2018
DOI: 10.2118/194224-ms
|View full text |Cite
|
Sign up to set email alerts
|

Pore Pressure Prediction in Unconventional Carbonate Reservoir

Abstract: Prediction of the formation pore pressure is considered as a significant simulation process during the drilling and production phases of the carbonate reservoir. The deficiency in this prediction allows for the occurrence of many troubles like blowouts, kicks, hole washouts, wellbore breakout, and stuck pipe. The most common conventional methods for the pore pressure prediction are Eaton's and Bower's methods which depend mainly on the normal compaction trend and commonly applied on Shales. The objective of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Stewart (1999) suggested that gas accumulations at shallow depths can cause enough overpressure to form set of faults and fractures with a circular structure. An important observation, however, is that the chalk reservoir of the Apollonia Formation is characterized by its low formation pressure (Elmahdy et al, 2018;Salah et al, 2016) which suggests the releasing of the formation pressure after the generation of the polygonal faults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stewart (1999) suggested that gas accumulations at shallow depths can cause enough overpressure to form set of faults and fractures with a circular structure. An important observation, however, is that the chalk reservoir of the Apollonia Formation is characterized by its low formation pressure (Elmahdy et al, 2018;Salah et al, 2016) which suggests the releasing of the formation pressure after the generation of the polygonal faults.…”
Section: Discussionmentioning
confidence: 99%
“…The Apollonia Formation (upper Paleocene to middle Eocene) is overlain by the Dabaa Shale (Oligocene), and is underlain by the chalk of the Khoman Formation (Upper Cretaceous) ( Figure 3). The Apollonia Formation was studied in detail in terms of its lithology, palaeontological characteristics and reservoir productivity (e.g., El-Bendary et al, 2016;Elmahdy, Farag, Tarabees, & Bakr, 2018;Salah, Orr, Abdel Meguid, Crane, & Squires, 2016;Sedek & Al Mahdy, 2013;Sousa & Badri, 1996).…”
Section: Geologic Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to estimate the in-situ stresses, several calculations were carried out with two types of calibrations on them. For the overburden, the density all over the overlying strata (shallow and not available in the logs) was extrapolated using a tie in the mudline [20] and the vertical stress integrates the effects of the water column with a fixed water density [1]. The pore pressure used was calculated from the Sonic Eaton model [21] and the normal pore pressure method [1], these calibrated with Modular Formation Dynamic Tester (MDT) data [22].…”
Section: In-situ Stressesmentioning
confidence: 99%
“…[2]. Pp estimation is based on Terzaghi principle and Biot law, where they are dealt with estimation of effective stress according to determined Pp, as well as, they accounted source of up-normal (over and under) pressure as disequilibrium compaction criteria [3].…”
Section: Introductionmentioning
confidence: 99%